KEDUDUKAN HUKUM UNIT POLISI SATWA DALAM MELAKUKAN PELACAKAN BARANG ILEGAL DI BANDARA BERDASARKAN PERATURAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 1 TAHUN 2019 - Wintara, Putu Yadnya (Kerta Dyatmika, 2023)
Based on the Regulation of the Chief of the Indonesian National Police Number 1 of 2019 concerning the System, Management, and Standards of Operational Success of the Indonesian National Police, the Police Canine Unit (K-9) holds a significant function in supporting law enforcement duties. A similar function is also regulated in the Regulation of the Director General of Customs and Excise Number PER-3/BC/2015 concerning Guidelines for the Management of Detector Dogs within the Directorate General of Customs and Excise. However, a legal issue arises concerning the authority and jurisdiction over K-9 units, as both regulations govern similar interests yet contain conflicting provisions regarding the use and command of K-9 units by different institutions. This research aims to examine the legal status of the Police Canine Unit in tracking illegal goods at airports, and to analyze the legal framework of such units under the Regulation of the Chief of the Indonesian National Police Number 1 of 2019. The type of research employed is normative legal research, focusing on statutory and regulatory approaches. The results indicate that the Police Canine Unit plays a crucial role in detecting illegal goods at airports; however, its deployment is not adopted within the Customs and Excise environment due to institutional differences in duties and functions. Furthermore, a normative conflict exists between the police and customs regulations regarding the management and operational authority of detector dogs. In conclusion, regulatory harmonization between institutions is necessary to prevent overlapping authorities and to enhance the effectiveness of the Police Canine Unit in combating illicit goods trafficking.